Smart materials: innovative strategies for oral-maxillofacial bone defects repair - Yu, Yilin; Liu, Zhenyuan; Qin, Xu; Song, Ke; Xu, Lianyi (Frontiers in Bioengineering and Biotechnology, 2025)
Oral-maxillofacial bone defects complicated by tumors, infections, or other bone diseases pose a significant clinical challenge. Traditional tissue-engineered bone substitute still has limitations regarding its three elements that resulting in unsatisfactory regeneration capability. Smart materials are a cutting-edge type of functional materials that can sense and respond to a wide range of environmental conditions or stimuli, including optical, electrical, magnetic, mechanical, thermal, and chemical signals. According to the type of stimulus to which the materials respond, they can be classified into externally stimulated materials and internally stimulated materials. This review, based on the latest advances in smart materials for bone defect repair, summarizes the different stimulus-responsive strategies of smart materials and the materials under each strategy. It also discusses the classic biomedical applications of these materials in the repair of oral-maxillofacial bone injuries in recent studies, compares the advantages and disadvantages of different strategies, and discusses the current challenges and future prospects of smart materials.